Two new species of Actinocladium Ehrenb. from India - G. SURESH KUMAR, B.S. REDDY and D.K. AGARWAL, C. MANOHARACHARY*, I.K. KUNWAR (Indian Phytopathology, 2010)
Two new species of Actinocladium Ehrenb. collected from forests of Andhra Pradesh, India are described. In Actinocladium vpagnihotrudui sp. nov. the conidia are 3-5 armed (arms 45-75 Âµm long) and verrucose, whereas in A. agumbense sp. nov. the conidia are verrucose and always 4 armed (arms 35-50 Âµm long).